Media Literacy and Adoption of Green Lifestyle for a Sustainable Future: A Study with Special Reference to Digital Literacy Campaign (International Journal of Food and Nutritional Sciences, 2023)
The research paper attempts to identify and delineate the role of greenlifestyle communication and media literacyin general and specific roles of participatory communication channels in meeting the goals of sustainability in particular for attaining a sustainable future both at local and global level. An Informed and conscious citizens can utilize green communication programmes effectively and successfully. Informed and conscious citizens can also play a responsible role in promoting media literacy culture and protection and preserving biodiversity in various walks of their lives. In fact, to fulfill the goals of sustainable development through protecting biodiversity, there is an indispensable need to mould a lifestyle that is environment friendly and equitable all over the world. Participatory green communication alone is not sufficient to meet these objectives but is a crucial element in facilitating the fulfillment of these objectives. Media is an intervening variable without which the materialization of different goals of sustainable development is not possible. Therefore, Media has the key role in facilitating the participation of people relating to sustainable development. The paper examines the role participatory media, people’s level of media literacy, green skill and application of that lifestyle in their everydaywalk of life for a sustainable future.